2017
DOI: 10.1177/0047287517702744
|View full text |Cite
|
Sign up to set email alerts
|

Am I a Backpacker? Factors Indicating the Social Identity of Chinese Backpackers

Abstract: The question of what constitutes backpacker identity has been one of the central topics of backpacking tourism research. With the economic boom in China, the last two decades witnessed the proliferation of Chinese backpackers. By adopting quantitative methods, this study provides a comprehensive understanding of what makes one a "backpacker" in China. Comparing results from t-tests, binomial logistic regression, and multiple linear regression, it is found that Chinese backpackers' social identities are mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 50 publications
2
59
0
Order By: Relevance
“…This indicated that the benefits of personal development, as well as perceived contributions to local communities, have been perceived to be the most important element in backpacker identity construction. This finding is in line with some previous narrative studies which confirmed that backpackers' identity stories powerfully consisted of their experience of self-change and responsible travel behaviors (e.g., Zhang et al 2018;.…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 3 more Smart Citations
“…This indicated that the benefits of personal development, as well as perceived contributions to local communities, have been perceived to be the most important element in backpacker identity construction. This finding is in line with some previous narrative studies which confirmed that backpackers' identity stories powerfully consisted of their experience of self-change and responsible travel behaviors (e.g., Zhang et al 2018;.…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…Recently, identity has gained increasing attention in travel and tourism research (e.g., , particularly in backpacker studies (e.g., S. Cohen 2011;Elsrud 2001;Zhang, Morrison, Tucker, and Wu 2018;Zhang, Tucker, Morrison, and Wu 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Backpackers have had a profound influence on the character of various places around the world, as their desire to travel ‘off-the-beaten-track’ has brought new destinations to the attention of the tourism industry (Hampton, 2013; Pryer, 1997; Westerhausen and Macbeth, 2003). Scholars have provided industry and community perspectives of backpacking (Hampton, 2013; Pryer, 1997; Welk, 2010), engaged with backpacker identity formation and experiences (Bui et al, 2014; Chen et al, 2019; Zhang et al, 2018), and considered the everyday practices of other tourist types (Edensor, 2007; Obrador, 2003). Yet, little is known of how the practices of backpackers contribute to place-making processes.…”
Section: Introductionmentioning
confidence: 99%